Analysis of Immature Platelet Fraction in Patients with Solid Tumors Undergoing Chemotherapy - Runtuwene, Aliza Virginia Eunike; Abdullah, Agus Alim; Arif, Mansyur (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2025)
Thrombocytopenia is a common side effect in patients undergoing chemotherapy. Examination of platelet count parameters alone cannot predict the platelet recovery response. Immature Platelet Fraction (IPF) can be used as an additional parameter to determine the etiology of thrombocytopenia. This study aimed to analyze IPF, and other platelet-related parameters related to the effects of chemotherapy on solid tumor patients. A prospective observational study design involving 35 solid tumor patients undergoing chemotherapy at Dr. Wahidin Sudirohusodo Hospital, Makassar, was carried out from August to September 2023. Platelet-related parameters (PLT, PDW, IPF, AIPF, and MPV) were measured using an automatic hematology analyzer. Kolmogorov-Smirnov, paired T-test, Wilcoxon, and Spearman test were used for statistical analysis. There was a significant difference in mean PLT, IPF, PDW, and MPV (p < 0.05) before and after chemotherapy. There was a positive correlation in differences in IPF, MPV and PDW (p < 0.001) with a strong correlation (r =0.6-0.8). There was a negative difference in IPF and PLT (p=0.068) with moderate correlation (r =0.312). Chemotherapy causes a significant decrease in platelets and a significant increase in IPF. Routine blood tests and IPF are useful for monitoring thrombocytopenia due to the effects of chemotherapy.